El cultivo de la habichuela en varios paises de America Latina - Janssen, W. (International Center for Tropical Agriculture, 1987)
Results from a survey on snap bean production, marketing, and consumption, carried out among the participants to the workshop on Snap Bean Improvement, held at CIAT (Colombia), coming from Argentina, Brazil, Peru, Ecuador, and Colombia, are presented. Although the area planted to snap beans in these countries is not that large, the production value is considerably high. The application of fertilizers, irrigation, herbicides, fungicides, and insecticides is rather frequent; constant chemical control is not only expensive but dangerous. Consequently, snap bean improvement can lower production costs and increase crop sanity. (CIAT)